A new species of Amolops Cope, 1865 (Anura, Ranidae) from central Guangdong, China - Song, Han-Ming; Wang, Fu-Xuan; Qi, Shuo; Wang, Hao-Tian; Lyu, Zhi-Tong; Cai, Yao-Yu; Zhu, Yun-Sheng; Zhong, Qi-Feng; Liu, Yang; Wang, Ying-Yong (Zootaxa, 2026)
In this study, a new species of the genus Amolops (Anura, Ranidae), Amolops guangzhouensis sp. nov., is described based on six type specimens collected from Conghua District, Guangzhou City, and adjacent Longmen County, Huizhou City, in Guangdong Province, China. The molecular phylogenetic analysis, based on two mitochondrial DNA fragments (16S and COI), places the new species as an independent evolutionary lineage within the A. daiyunensis group. The morphometric statistical analysis and morphological comparison also distinguish the new species from all other congeners. This species can be differentiated from those close relatives by dorsal surface pattern, tiny translucent white spinules across skin, indistinct supernumerary tubercle below fingers, prominent tarsal gland and tarsal fold, and nuptial pad coloration. The discovery of this new species adds to the growing diversity of this genus and represents the westernmost distribution occurrence of the A. daiyunensis group, implying the species diversity of Amolops in southeastern China might still be underestimated.